A prospective, randomized, within‐subject study of ALA‐PDT for actinic keratoses using different irradiation regimes. Issue 5 (24th May 2018) - Zaar, Oscar; Sjöholm Hylén, Alexandra; Gillstedt, Martin; Paoli, John
Summary: Background: Photodynamic therapy (PDT) can be used to treat large fields of actinic keratoses (AKs) with high clearance rates. A notable downside is the amount of pain that accompany the treatment. This study aimed to optimize the illumination protocol during conventional PDT in order to reduce pain without compromising treatment effectiveness. Methods: In this prospective, randomized study with a split‐face design, patients with, symmetrically distributed AKs were included. All patients were treated using a ALA 78 mg/g gel. One side was illuminated with the Aktilite ® CL‐128 lamp and the other side with the RhodoLED ® lamp in which the light intensity gradually increased to a maximum of 60%. Both sides received a total light dose of 37 J/cm 2 . Pain during the treatment was measured using a visual analogue scale. The clinical effectiveness of the 2 treated sides was assessed after 12 weeks. Results: Twenty‐nine patients with 399 AKs were included. Illumination with the gradually increasing light intensity resulted in a decrease in the median visual analogue scale score by 1.1 points. Clearance rates were similar between the 2 lamps. Conclusion: Minimizing the light intensity during the illumination phase of PDT reduces pain, while still preserving a high clearance rate of AKs.